PERSEPSI MASYARAKAT KOTA SOLOK MELALUI KOMUNIKASI PUBLIK: UPAYA MENINGKATKAN PARTISIPASI PEMILIH PADA PEMILU TAHUN 2024: Society Perception of Solok City Through Public Communication: Efforts to Increase Voter Participation in the 2024 Elections - Zona Rida Rahayu; Ismail Arifin (ASOSIASI IDEBAHASA KEPRI, 2023)
In carrying out its duties as the AdhoC Committee on duty, deliver information to the people of the city of Solok. The information conveyed is that the public has come to give their right to vote in the 2024 election. Since the public has various perceptions in responding to various issues, proper communication is needed so that the information is right on target. The methods used in this service are lectures, questions and answers, and discussions. Lectures are carried out in conveying public perception material through public communication. This activity was held on Tuesday 24 January 2023 at the Multipurpose Hall of the Rocy Hotel, Bukittinggi City. This activity was attended by 49 members of the Ad HoC Committee for election organizers at the KPU in Solok City, consisting of 10 members of the District Selection Committee and 39 members of the Voting Election Committee. The communication referred to here is the use of appropriate strategies in communicating. The results of this service explain to the Ad HoC Paitian about various strategies that can be used to communicate. These strategies are the 5S (smile, greet, be patient, polite, and simple), love languages, listen 100%, and like or dislike.